Fatty Acid Composition of Unicellular Strains of Blue-Green Algae - Kenyon, C. N. (1972)
The fatty acids of 34 strains of unicellular blue-green algae provisionally assigned to the genera Synechococcus, Aphanocapsa, Gloeocapsa, Microcystis, and Chlorogloea by Stanier et al. have been chemically characterized. The strains analyzed can be divided into a series of compositional groups based upon the highest degree of unsaturation of the major cellular fatty acids. Twenty strains fall into the group characterized by one trienoic fatty acid isomer (α-linolenic acid), and seven strains fall into a group characterized by another trienoic acid isomer (γ-linolenic acid). These groups in many cases correlate well with groupings based upon other phenotypic characters of the strains, e.g., deoxyribonucleic acid base composition. The assignment of a strain to a compositional group is not altered when the strain is grown under a variety of different culture conditions. All strains contain glycolipids with the properties of mono- and digalactosyldiglycerides.